How long-run effects of local demand shocks on employment rates vary with local labor market distress - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2021)
This paper estimates that long-run changes in a county's prime-age employment rate are significantly affected by labor demand shocks to both the county and its overlying commuting zone (CZ). The overall benefits of labor demand shocks are due more to CZ demand shocks than county demand shocks. A lower preexisting county employment rate increases the effects of CZ demand shocks. Simulations suggest that low prior employment rate CZs, versus higher-rate CZs, will have much larger employment rate effects from demand shocks. Targeting jobs at more distressed counties within a CZ has modest effects, much lower than the effects of targeting jobs at more distressed CZs.
Keywords: R23; 330; Local labor markets; job creation benefits; local labor demand; regional distress